Recruitment and Selection Impact on Employee Performance: A Quantitative Analysis: Dampak Rekrutmen dan Seleksi terhadap Kinerja Karyawan: Analisis Kuantitatif - Aufa Herely Tata Dinanty; Vera Firdaus (Academia Open, 2024)
This study aims to investigate the influence of recruitment and selection processes on employee performance, utilizing a quantitative associative approach. The research involves 100 employees from Pizza Hut Sidoarjo and employs primary and secondary data along with multiple linear regression analysis techniques. The findings reveal that both recruitment and selection significantly affect employee performance, underscoring the critical role of these HR practices in building a competent workforce. This research emphasizes the importance of strategic human resource management in enhancing employee performance across industries.Highlights : This study explores the impact of recruitment and selection processes on employee performance. Multiple linear regression analysis is used to analyze data from 100 employees at Pizza Hut Sidoarjo. The research highlights the crucial role of strategic human resource management in enhancing workforce competence and performance. Keywords: recruitment, selection, employee performance, human resource management, quantitative analysis